Insights Into First Grade Students' Development of Conceptual Numerical Understanding as Drawn From Progression-Based Assessments - Balt, Miriam; Fritz, Annemarie; Ehlert, Antje (Frontiers in Education, 2020)
Early numeracy has been found to be one of the strongest predictors for later success in learning. Equipping children with a sound conceptual numerical understanding should therefore be a focus of early primary school mathematics. Assessments that are aligned to empirically validated learning progressions can support teachers to understand their students learning better and target instruction accordingly. This study examines numeracy learning of 101 first grade students over the course of one school year using progression-based assessments. Findings show that the students’ performance increased significantly over time and that the initial conceptual numerical understanding had a positive effect on the students’ learning progress as well as their end of school year performance. Analyzing the performance data based on the levels of the underlying developmental model uncovered an increasing qualitative elaboration of conceptual numerical understanding over time, but also individual differences within this process that need to be addressed through targeted intervention.